Multimodal neuromonitoring - Macas, Andrius; Bilskienė, Diana; Gembickij, Aleksandr; Žarskus, Ainius; Rimaitis, Marius; Vilkė, Alina; Šuškevičienė, Ilona; Rugytė, Danguolė; Tamašauskas, Arimantas (Acta medica Lituanica, 2012)
The goal of the intensive care management of a neurosurgical patient is to preserve adequate cerebral perfusion, oxygenation and metabolism in order to prevent secondary neurological injury. In preventing secondary neurological insults interventions must be started early. For many years conventional methods of neuromonitoring have proved their efficacy. However, their sensitivity in detecting subtle metabolic derangements in the real time manner is low and the valuable time for the appropriate treatment is lost. In recent years, there are numerous study data suggesting that implying of advanced neuromonitoring techniques can improve outcomes. Moreover, it helps to guide goal-directed therapy. Although data on advanced neuromonitoring are preliminary and mostly observational, the number of modern neurosurgical centers applying it as a standard is high. With the increasing technical possibilities, the concept of multimodal neuromonitoring is of increasing popularity. Multimodal neuromonitoring allows continuous real time assessment of cerebral perfusion, oxygenation, metabolism and global function which makes it attractive and promising in clinical practice.
Keywords: neuromonitoring; multimodal; traumatic brain injury; ce rebral metabolism